2015
DOI: 10.1175/mwr-d-13-00321.1
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble Sensitivity Analysis Applied to a Southern Plains Convective Event

Abstract: Forecast sensitivity of an April 2012 severe convection event in northern Texas is investigated with a highresolution Weather Research and Forecasting (WRF) Model-based ensemble Kalman filter (EnKF). Through ensemble sensitivity analysis (ESA), which relates a forecast metric to initial and early forecast errors by linear regression, features of the flow are revealed that reflect dynamical relationships with the forecast convection. Results indicate that ESA can be successfully applied to high-resolution forec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 33 publications
1
33
0
Order By: Relevance
“…The results for this study have some intriguing implications for CI forecasts along the dryline during days without any clear feature to focus CI. Similar to previous sensitivity studies, convective forecasts appear to be sensitive to thermodynamic fields and boundaries; however, unlike these previous studies, the position of these boundaries does not appear to be tied to the position of larger-scale synoptic features that might be expected to modulate the environment (e.g., Bednarczyk and Ancell 2015;Torn and Romine 2015;Berman et al 2017;Hill et al 2016). Moreover, these convective forecasts appear to be most sensitive to the water vapor above the boundary layer; however, the results here suggest that the evolution of water vapor is not merely the advection of initial condition uncertainty.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…The results for this study have some intriguing implications for CI forecasts along the dryline during days without any clear feature to focus CI. Similar to previous sensitivity studies, convective forecasts appear to be sensitive to thermodynamic fields and boundaries; however, unlike these previous studies, the position of these boundaries does not appear to be tied to the position of larger-scale synoptic features that might be expected to modulate the environment (e.g., Bednarczyk and Ancell 2015;Torn and Romine 2015;Berman et al 2017;Hill et al 2016). Moreover, these convective forecasts appear to be most sensitive to the water vapor above the boundary layer; however, the results here suggest that the evolution of water vapor is not merely the advection of initial condition uncertainty.…”
Section: Discussionsupporting
confidence: 61%
“…As a consequence, this study employs the maximum vertical kinetic energy [( 1 /2)w 2 max , where w max is the maximum vertical motion in a column) forecast metric averaged over a geographic area and time period (hereafter J VKE ). 1 This metric has been used in previous studies (e.g., Berman et al 2017) and unlike precipitation or reflectivity-based metrics, which have been used in other sensitivity studies (e.g., Bednarczyk and Ancell 2015;Torn and Romine 2015;Hill et al 2016), it is relatively straightforward to separate convection from extensive stratiform precipitation. Moreover, the time period of the greatest variability in this metric occurs between 22 and 25 h (2200-0100 UTC); therefore, this time period is used in the metric calculation.…”
Section: Maymentioning
confidence: 99%
See 2 more Smart Citations
“…A linear regression of a chosen metric valid later in the forecast window, such as accumulated precipitation, is performed onto the perturbed initial-condition variable (e.g., soil moisture). Numerous ESA studies have shown significant and useful linear relationships between initial-condition variables and forecast variables, even when the chosen metric involves storm-scale variables and substantial nonlinearity (Bednarczyk and Ancell 2015;Hill et al 2016). Figure 9 shows an example of how ESA can discriminate real dynamical processes from unrealistic ones created through chaos seeding.…”
mentioning
confidence: 99%